1997
DOI: 10.1136/gut.40.6.761
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular dysfunction in patients with inflammatory bowel disease treated with aminosalicylate.

Abstract: Background-An increasing number of case reports indicate potential nephrotoxicity of 5-aminosalicylic acid (5-ASA), which shares similarities with the chemical structures of both phenacetin and acetylsalicylic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 31 publications
3
67
1
1
Order By: Relevance
“…Finally, some authors have concluded that an increased prevalence of tubular proteinuria may be attributed to high doses of 5-ASA. 15 Nevertheless, differences between results reported in these studies may relate to differences in disease activity of IBD. In this respect, microalbuminuria values have been shown to fall when the disease is quiescent, 9,10 even though the patients were receiving 5-ASA treatment.…”
Section: Proteinuria In Patients With Ibdmentioning
confidence: 95%
“…Finally, some authors have concluded that an increased prevalence of tubular proteinuria may be attributed to high doses of 5-ASA. 15 Nevertheless, differences between results reported in these studies may relate to differences in disease activity of IBD. In this respect, microalbuminuria values have been shown to fall when the disease is quiescent, 9,10 even though the patients were receiving 5-ASA treatment.…”
Section: Proteinuria In Patients With Ibdmentioning
confidence: 95%
“…ALP is phosphohydrolase enzyme, attached with glycosyl phosphatidyl inositol, anchors to the cell wall and its activity is considered as an important hallmark for inflammation during the UC (Schreiber et al 1997). The elevated levels of ALP support the inflammatory changes in UC.…”
Section: Discussionmentioning
confidence: 99%
“…An area that has yet to be addressed relates to the influence of IBD medications on protein abundance levels. Schreiber et al [47] reported the possible link between high dose 5aminosalicylic acid (5ASA) and modulated urinary protein concentrations. However, other groups have suggested that these urinary pro teins reflect renal extraintestinal manifestations rather than 5ASA toxicity [48,49] .…”
Section: Fecal Calprotectinmentioning
confidence: 99%